On the log-convexity of the difference sequence of a log-convex sequence - Zhao, Feng-Zhen (Sarajevo Journal of Mathematics, 2022)
Let {z_n}_n0 be a log-convex sequence, where z_n+1-z_n>0 for n0. In this paper, we give several sufficient conditions for the log-convexity of the sequence {z_n+1-z_n}_n0. As applications, we discuss log-convexity for a series of sequences involving derangement numbers, Motzkin numbers, Fine numbers, numbers of counting directed animals, and so on.